2011
DOI: 10.1111/j.1365-2494.2011.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hygienic quality of haylage fed to healthy horses

Abstract: Wrapped forages such as haylage and silage are increasing in popularity in equine feed rations, but knowledge of their microbial composition, especially of haylage, is scarce. Haylage may be more at risk of mould growth compared to silage, and methods for the assessment of hygienic quality of haylage are needed. Varying culturing conditions, including aerobic ⁄ anaerobic incubation, four substrates and three incubation temperatures were therefore evaluated for analysis of fungi in haylage samples from eighteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…DG18 is, however, also well suited for detection of fungi in samples with lower water activity, such as the genera Aspergillus and Penicillium, due to high concentration of sodium chloride or carbohydrates. In a previous study of hygienic quality assessment of wrapped forage with DM content at 653 (SD 89.9) g/kg, these genera were among the most common genera in the samples (Müller, Hultén, & Gröndahl, ). Müller et al.…”
Section: Introductionmentioning
confidence: 91%
“…DG18 is, however, also well suited for detection of fungi in samples with lower water activity, such as the genera Aspergillus and Penicillium, due to high concentration of sodium chloride or carbohydrates. In a previous study of hygienic quality assessment of wrapped forage with DM content at 653 (SD 89.9) g/kg, these genera were among the most common genera in the samples (Müller, Hultén, & Gröndahl, ). Müller et al.…”
Section: Introductionmentioning
confidence: 91%
“…The samples were immediately stored at 4 to 6°C before analysis, which was conducted later the same day. Sampling was performed, according to literature (Müller et al, 2011), by a limited number of people (the authors ET and GB). The same sampling protocol was followed at the same sampling time in each farm to avoid differences in sampling procedure that could have influenced the analytical result.…”
Section: Bale Sample Collectionmentioning
confidence: 99%
“…Table 2 Average microbial composition (log CFU/g) in silage, haylage, and hay after 3 and 12 months of storage, and interaction effects of forage type (silage, haylage, and hay) and storage time (lower detection limit log 1.5 CFU/g for yeast and mold, log 1.7 for lactic acid bacteria, clostridia, and enterobacteria). In a study of haylage bales on commercial horse farms, a trend for decreasing mold counts (P ¼ .06) from OctoberNovember 2007 to May-June 2008 was reported [31]. Increased storage time resulted in decreased mold counts in hay in the present study, but hay contained greater mold counts than silage and hay at all sampling occasions.…”
Section: Influence Of Storage Time On Microbial Composition Of Foragesmentioning
confidence: 73%
“…Previous investigations of effects of increased storage time of wrapped forage bales did not include counts of LAB [23,31] but reported that pH and content of lactic acid in silage and haylage, which are products of LAB activity, decreased (pH) and increased (lactic acid content) from 2 to 14 months of storage [23], which was probably due to continued growth and/or activity of LAB in the forage during storage. The reason for decreased LAB counts with increased storage time in silage and haylage in the current study remains to be explained, but lack of energy substrates or too low pH in the forages is not a likely explanation given the comparatively high DM content in both haylage and silage, resulting in restricted lactic acid fermentation [23,29].…”
Section: Influence Of Storage Time On Microbial Composition Of Foragesmentioning
confidence: 96%
See 1 more Smart Citation